2005
DOI: 10.1111/j.1399-6576.2005.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroperative depth of anaesthesia may influence postoperative opioid requirements

Abstract: The results indicate that the peroperative depth of anaesthesia may have effects on the postoperative analgesic requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 12 publications
1
21
1
Order By: Relevance
“…The result of their study shows that patients maintained in the lighter plane of anesthesia intraoperatively activated the patient controlled anesthesia (PCA) pump more frequently than those maintained in deeper plane during the first 24 postoperative hours. [5] In these studies, authors speculated that intraoperative deeper plane of anesthesia may have partially aborted the noxious stimuli, influencing the postoperative pain intensity and analgesic requirement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of their study shows that patients maintained in the lighter plane of anesthesia intraoperatively activated the patient controlled anesthesia (PCA) pump more frequently than those maintained in deeper plane during the first 24 postoperative hours. [5] In these studies, authors speculated that intraoperative deeper plane of anesthesia may have partially aborted the noxious stimuli, influencing the postoperative pain intensity and analgesic requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have shown that adequate intraoperative depth of anesthesia is associated with less postoperative pain and decreased analgesic requirements. [56] The use of clinical signs may not reliably measure the hypnotic component of anesthesia, as they can be affected by factors such as blood volume, cardiac contractility, and drug effects on the cardiovascular system. [7] Bispectral index (BIS) provides a continuous age-independent monitoring of hypnotic state induced by the most widely used sedative-hypnotic agent and has been used to assess the induction quality, depth of anesthesia, intraoperative requirement of anesthetics, postoperative recovery, and to reduce the incidence of intraoperative recall awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing the two anaesthetic methods are equivocal, with a tendency towards superiority in the TIVA groups in terms of less nausea and earlier start of oral fluid intake (Fassoulaki, 2008;Kroon, 2010). A recent study suggests that deep levels of intraoperative sedation (as measured by auditory evoked potentials) may reduce postoperative morphine demands (Henneberg, 2005). It was conducted using TIVA, but it remains unknown if a similar relationship may be seen with inhalational agents.…”
Section: Anaesthetic Techniquementioning
confidence: 99%
“…Several methods have been proposed to assess and quantitate the nociceptive response during general anesthesia [8][9][10][11] Autonomic nervous system measures, for example Heart Rate Variability (HRV) [12] or Skin Conductance (SC) [13] and parameters extracted, have been proposed and used by several authors. HRV and SC are correlated with sympathetic activity and therefore, monitors based on these parameters can measure the increase in sympathetic activity.…”
Section: Introductionmentioning
confidence: 99%